A chimeric mutant analysis in yeast cells suggests BiP independent regulation of the mammalian endoplasmic reticulum-stress sensor IRE1α - Mai, Thanh Chi; Munakata, Takeo; Tran, Duc Minh; Takagi, Hiroshi; Kimata, Yukio (Bioscience, biotechnology, and biochemistry, 2018)
An endoplasmic reticulum (ER)-located transmembrane protein, Ire1, triggers cytoprotective events upon ER stress. Chimeric yeast Ire1 carrying the luminal domain of the mammalian major Ire1 paralogue IRE1α is upregulated in ER-stressed yeast cells, but is poorly associated with the ER-located chaperone BiP even under non-stressed conditions. This observation contradicts the theory that BiP is the master regulator of IRE1α.